High-Performance Generator for a New Generation of Aircrafts - Flur Ismagilov; Irek Khayrullin; Vyacheslav Vavilov; Ruslan Karimov; Anton Gorbunov (Institute of Advanced Engineering and Science, 2017)
The article describes multidisciplinary design process of high-performance electric generator for advanced aircrafts by analytical methods and computer modeling techniques (electromagnetic, thermal and mechanical calculations). New technical solutions used in its development are described. The main ideas are revealed of the method of EG voltage stabilization we used. To improve the heat dissipation efficiency, we have developed a new cooling system, and provide its study and description in this paper. The advantages of this cooling system include the fact that EG is made with dry, uncooled rotor. This allowed eliminating additional pumps, and significantly reducing the size of CSD. According to the results of our study, we created an experimental full capacity layout, and its studies are also provided in this paper.